TKDN SELF-ASSESSMENT OF REVERSE-ENGINEERED COAL PIPE FABRICATION AT PLN PUSHARLIS: A CASE STUDY - Elviena Farizka; Muhamad Habibi; Heryanto (Bulletin of Engineering Science, Technology and Industry, 2026)
Dependence on imported spare parts in coal-fired power plants increases procurement cost and delivery time, while critical components such as the Coal Pipe are exposed to abrasive wear and elevated operating temperatures. This study evaluates the Domestic Component Level (Tingkat Komponen Dalam Negeri/TKDN) of an SS400 Coal Pipe fabricated by PLN Pusharlis through reverse engineering. A case-study self-assessment was conducted by integrating engineering documents, manufacturing flow, shop drawings, bill of materials, procurement realization, labor, and factory-overhead data with the cost-classification approach required by Indonesian Ministry of Industry Regulation No. 16/M-IND/PER/2/2011. The fabrication approach references ASTM G65 for abrasion-related material considerations and ASME Section IX for welding qualification. The detailed production-cost structure totals IDR 39,571,487.44, consisting of IDR 24,551,412.26 domestic components and IDR 15,020,075.18 foreign components, resulting in a TKDN value of 62.04%. The foreign share is concentrated mainly in primary raw materials, whereas direct labor, indirect labor, and most overhead are domestically sourced. The case demonstrates that reverse engineering can support import substitution while providing an auditable basis for domestic-content accountability